Trans‐right ventricle metabolite gradients in obesity highlight multiple metabolic pathways - Hanna M. Knauss; Mythri Ambatipudi; Leah B. Kosyakovsky; Matthew S. Herzig; Jessica K. Wang; Elizabeth E. Liu; Emily S. Lau; Jenna N. McNeill; Xu Shi; Robert E. Gerszten; Naomi M. Hamburg; Gregory D. Lewis; et al. (Physiological Reports)
Abstract Obesity and metabolic dysfunction are associated with pulmonary vascular remodeling, yet molecular mechanisms remain poorly understood. We sought to study trans‐right ventricular (RV) metabolite gradients to elucidate potential molecular pathways operant among individuals with obesity and pulmonary hypertension. In this study, 38 individuals with obesity (mean age 58 years, 68% women, average BMI 36.6 kg/m2) underwent invasive right heart catheterization. Multi‐site blood sampling from the superior vena cava and pulmonary artery was performed to assess trans‐RV gradients, with targeted metabolite profiling using liquid chromatography‐mass spectrometry. We found 56 metabolites with significant trans‐RV gradients (FDR q < 0.05), including intermediates of fatty acid oxidation, the tricarboxylic acid cycle, and nucleotide metabolism. Further, trans‐RV gradients in lipid and purine metabolism were associated with BMI and related cardiometabolic traits, such as waist circumference, insulin resistance, and serum lipids. Finally, differential levels of bile acids, intermediates of lipid peroxidation, and nucleotide metabolism across the RV were associated with pulmonary hypertension. In conclusion, trans‐RV metabolite gradients among individuals with obesity reveal alterations in metabolites representative of molecular pathways such as fatty acid oxidation, and others correlated with cardiometabolic traits and/or pulmonary hypertension, including orotic acid, bile acids, and acylcarnitines.